Harmonizing Trade And Environment Conflicts: Win, Lose Or Draw - Audrey, Liwan; Khalid, Abdul Rahim (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Internalization of environmental externalities through the Polluter-Pays-Principle (PPP) has been widely encouraged. Under the PPP, it is generally assumed that the additional cost of internalization is passed on to consumers. However, stiff competition in the world market could make it difficult for exporters to pass on to international consumers, thus profit margin on export commodities is eroded and exports may be curtailed. This situation prevails in many developing countries which export a large proportion of their commodity production. When pollution control costs are substantial, voluntary implementation of environmental policy in the commodity export sector of a country may be problematic. Some forms of international coordination are required to ensure that the costs of internalization of externalities are accounted for in the price of the commodity. An international commodity-related environmental agreement (ICREA) provides an institutional form for dealing with full cost pricing of commodities through international policy coordination for a win-win solution. Lessons from the theoretical aspects and empirical work on international environmental agreements are deliberated at government agencies, non-governmental organizations, businesses and tertiary institutions. Studies have shown mixed results that generalizations on the trade impacts of environmental regulations are unwise. Thus, trade and environment linkages remain an issue which calls for a political economic solution in the short term.